Anal membrane: varied presentations - Basu, Syamantak; Makan, Apoorva; Tulsian, Akriti; Joseph, Vini; Gandhi, Suraj; Shenoy, Neha Sisodiya; Shah, Hemanshi (International Surgery Journal, 2021)
An anal membrane is categorized as a low anorectal malformation and is noted under rare malformations in the International classification. It is very rare and may present variedly in different age groups and only a handful of cases have been ever described. It is one of the few anorectal malformations in which the anal canal is at a normal position, thus concealing itself from an attendant who is not suspicious. We present two cases of anal membrane. A newborn girl presenting at birth was treated by primary excision of the membranes. The second case was a 2 year boy with chronic constipation with an obstructive web of a persistent ruptured anal membrane. Both were short procedures with almost no morbidity. Both the cases would have been diagnosed earlier if the primary attendant had done a rectal examination. There was good post-operative outcome in terms of continence and constipation in both the cases. Neither of them needed any anal dilatations. Anal membrane is a rare low anorectal malformation which needs keen suspicion for diagnosis. It is easy to miss it if the attendant omits a rectal examination. Therefore, it is imperative to do a rectal examination of all neonates with non-passage of meconium and as well as children with chronic constipation.